Positioning and status of the Spanish numismatic journals in scientific databases (2019)
The following article captures the current situation of the Spanish scientific journals focused on numismatics and their positioning in the main international bibliographical (Latindex, Web of Science and Scopus) and Spanish databases (Dialnet and CIRC) through a comparative analysis of their distinctive characteristics and fundamental metrics (Google Scholar H5 index and their scores in MIAR). The results obtained determine that within this group has excelled in a prominent place the Revista Numismática Hécate, the only Spanish publication on this subject that has managed to be indexed in high impact databases such as the Web of Science and Scopus.